PENGARUH MODIFIKASI CDI DC TOTAL LOSS TERHADAP TORSI DAN DAYA PADA MOTOR DRAG SUZUKI SATRIA 120R - , M HILMAN HIDAYAT, Ir. Greg Sukartono ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Ignition system is a system that produces high voltage at the ignition coil which is channeled into the spark plug until there is an electric spark jumps. Electrical spark jumps are used to burn the fuel and air mixture in the combustion chamber. The presence of electrical sparks are one of the requirements for the machine can work. Ignition system used on Suzuki Satria 120R motorcycle CDI ignition system (Capacitive Discharge Ignition). CDI ignition system used in this because it has many advantages, among others, dirty spark plugs are not easy because of the high voltage ignition coil and stable performance of the engine at low speed is very good because they are distraced by a sparks jumps on platinum, maintenance is easier because it does not need to be corrected due to wear of the platinum contact points or heel (heel arm), and the spark jumps the spark plugs are relatively larger and balance of rotation both high and at lowspeed. Basically the ignition system consists of several main components namely battery, CDI unit, pulser coil (pick-up coil), coil ignition, and spark plugs. The fungtion battery as a source of current and pulse coil serves as the signaller to the CDI unit and set the ignition timing. CDI unit serves as a distributor and ignition coil while the circuit breaker serves to generate a high voltage which then generate a high voltage which then generate electrical sparks at the spark at the plug and used to burn the fuel and air mixture in the combustion chamber that has been compressed. The machine that we use for this Final regulations will be enabled to dragmatic then we make changes increase the power of the machine. Changes that do include raising the engine cylinder capacity of 120 cc, and particularly on the ignition unit we use a system of Total Lost to reduce the burden suffered by the magnet due to charging and lighting systems. To improve the performance of the machine, we use the CDI standard Shogun 110.